Bertolt Brecht's Main Concerns in Mother Courage and Her Children (Journal of the College of Basic Education, 2023)
Mother Courage and her Children is one of the great theatricalproductions during the Second World War . It represents Bertolt Brecht’sserious attempt to criticize war and capitalism at a time when crueldictators such as Hitler were shedding blood mercilessly .This study concentrates on Brecht’s major issues and his moralconcerns that he tackles in Mother Courage and her Children. We’ll tryto show how and why Brecht attacks war and its consequences . Thestudy consists of three sections. Section I is an introduction in whichsome light is shed on Brecht’s contribution to the epic theatre. It is alsotalks briefly about Brecht’s artistic d evelopment and his achievements.Section II is devoted to the critical analysis of Mother Courage and herChildren in relation to Brecht’s major concerns in this play . Some closereferences to the play are made to support our argument . To enrich ouranalysis some critical views are investigated . Section III gives aconclusion to the whole study and sums up its findings .